Chronic psychosocial stress makes rats more ‘pessimistic’ in the ambiguous-cue interpretation paradigm - Papciak, Justyna; Popik, Piotr; Fuchs, Eberhard; Rygula, Rafal (Behavioural brain research, 2013)
•We investigated whether negative judgement bias in rats can be induced psychosocially.•Rats were subjected to chronic social defeat in the resident–intruder paradigm.•Cognitive judgement bias was measured in the ambiguous-cue interpretation tests.•Rats subjected to chronic psychosocial stress are ‘pessimistic’. Human decisions are often biased by emotions. Stressed and depressed individuals tend to make negative, pessimistic judgements while those in positive affective states are often more optimistic. Chronic psychosocial stress has previously been shown to induce a spectrum of behavioural and physiological changes in rats that are considered the correlates of depressive symptoms in humans. In this study, we investigate whether chronic social defeat makes animals more ‘pessimistic’. To measure the changes in cognitive judgement bias, we applied the ambiguous-cue interpretation paradigm. In the operant boxes, the rats were trained to press one lever in response to one tone to receive a reward and to press another lever in response to a different tone to avoid punishment. Cognitive bias was tested by measuring the pattern of animals’ responses to a tone of intermediate frequency (ambiguous-cue). To induce chronic psychosocial stress, we subjected the animals to daily social defeat in the resident–intruder paradigm for 3 weeks. We report that chronic psychosocial stress makes rats more pessimistic.